The Effect of Inflation and Economic Growth on The Open Unemployment Rate in West Indonesia - Rembulan, RT. Anugrah Fitri; Bado, Basri; Astuty , Sri; Syafri, Muhammad; Irwandi (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of inflation and economic growth on the open unemployment rate in Western Indonesia. The research method used is panel data analysis with a fixed regression model approach, which involves processing data from several provinces in the region during a certain period. The results of the analysis show that economic growth has a significant effect on reducing the unemployment rate, while inflation does not have a significant effect on unemployment in the study area. The interpretation of these results shows that increased economic activity can reduce unemployment, while fluctuations in inflation do not directly affect the unemployment rate substantially. The conclusion of this study emphasizes the importance of strengthening economic growth as an effort to control unemployment, while the effect of inflation is relatively insignificant in the context of Western Indonesia.